Evolutionary adaptation of probiotics in the gut: selection pressures, optimization strategies, and regulatory challenges - Julia Leeflang; Josephine A. Wright; Daniel L. Worthley; M. Omar Din; Susan L. Woods (npj Biofilms and Microbiomes)
Abstract Probiotics and live bacterial therapeutics are garnering increased attention for use in human health and have the potential to revolutionise the treatment of gastrointestinal diseases. However, a pervasive feature of bacteria that must be considered in the design of safe and effective probiotics and live bacterial therapeutics is their capacity for rapid evolution, both at the individual (epi)genetic level and in terms of population dynamics. Here we summarise gastrointestinal-specific evolution of bacteria, focussing on genetic and population levels of adaptation to factors such as carbon source availability, environmental stressors, and interactions with the native microbiome. We also address regulatory and safety considerations for the development of probiotics and live biotherapeutics from an evolutionary perspective, with a discussion of methods that utilise evolution to improve probiotic safety and efficacy via directed evolution, in comparison to another popular approach, genetic engineering.